2018
DOI: 10.1007/s00404-018-4767-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal obesity on labor induction in postdate pregnancy

Abstract: NCT02788305.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
3
11
0
5
Order By: Relevance
“…They are less likely to have spontaneous labour and tend to have postterm pregnancy, as shown in previous studies [39,40]. In addition to the increased frequency of obstetric morbidities, such as GDM and hypertensive disorders among obese women which is directly associated with the increased need of IOL, moreover, they are more likely to experience failure of IOL and an increased risk of CS delivery compared to normal weight women [41,42]. This may be explained by the abnormal uterine contractions and dysfunctional labour noticed among obese women [43].…”
Section: Discussionmentioning
confidence: 72%
“…They are less likely to have spontaneous labour and tend to have postterm pregnancy, as shown in previous studies [39,40]. In addition to the increased frequency of obstetric morbidities, such as GDM and hypertensive disorders among obese women which is directly associated with the increased need of IOL, moreover, they are more likely to experience failure of IOL and an increased risk of CS delivery compared to normal weight women [41,42]. This may be explained by the abnormal uterine contractions and dysfunctional labour noticed among obese women [43].…”
Section: Discussionmentioning
confidence: 72%
“…Our study is the first cross-sectional study investigating high-risk pregnancy -induction of labor outcomes with misoprostol vaginal insert in obese on-term or late-term patients. Previous studies on the effect of maternal obesity on labor induction evaluated only the late-term pregnancies, induced by multiple therapy protocols with misoprostol, by amniotomy and oxytocin infusion (Maged et al, 2018) [3 -7, 31, 38-40]. Viteri et al (2020) [41] reported this year on nulliparous obese women with IOL, using combined Foley balloon and misoprostol, resulted in similar C-section rates compared to ripening with vaginal misoprostol alone.…”
Section: Strengthsmentioning
confidence: 99%
“…4 Women with obesity receive more medical interventions during their labors, 5 have slower labors, 6,7 and have a higher risk of cesarean birth, with rates up to 5 times higher than rates of women with a normal body mass index (BMI). 8,9 Safe prevention of cesarean birth in women with a high BMI is especially important, as this population is also at increased risk of morbidity and mortality following cesarean birth. [10][11][12][13][14] The aim of this study was to evaluate the effectiveness of the unit-level presence of midwives on the odds of cesarean birth in women of different BMI ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 27.1% of women in the United States are obese prior to pregnancy, and in non‐Hispanic black women, the prevalence of obesity is even higher, approaching 40% . Women with obesity receive more medical interventions during their labors, have slower labors, and have a higher risk of cesarean birth, with rates up to 5 times higher than rates of women with a normal body mass index (BMI) . Safe prevention of cesarean birth in women with a high BMI is especially important, as this population is also at increased risk of morbidity and mortality following cesarean birth .…”
Section: Introductionmentioning
confidence: 99%